Regulation of Transcription Factor YAP-TEAD by Non-coding RNA LINC00857 and the Inhibitory Effects on Ovarian Cancer Cell Proliferation: Non-coding RNA LINC00857 Effects on Ovarian Cancer - Lin, Xueke; Li, Ping; Feng, Dilu; Zheng, Jinyang; Chen, Guilian; Wu, Xiaohui; Dong, Zhenzhu; Lv, Yuchun (Cellular and Molecular Biology, 2022)
This study was aimed to explore the expression and mechanism of the transcription factor YAP-TEAD in the Hippo signaling pathway under the regulation of non-coding Ribonucleic Acid (RNA) LINC00857 in the proliferation of ovarian cancer cells, so as to provide a scientific research basis for clinical diagnosis and treatment of ovarian cancer. In the study, the ovarian cancer cell lines (BT 549) were rolled into a control group (normal culture-defined as BT549/NC) and a response group (transfected with non-coding RNA LINC00857 cultured cells-defined as BT 549YAP cells). The expression and proliferation ability of the transcription factor YAP-TEAD in the two groups of cancer cells were analyzed and compared. The results showed that the YAP-TEAD expression rate was the highest in Bt549 cells; the YAP content grade (0.18) in BT 549-YAP cells was lower than BT 549/NC (0.2) after transfection (P< 0.05); and the apoptotic rate of the response group (80%) was higher than that of the control group (25%) after the intervention. With the extension of culture time, the expression of CCN1 mRNA decreased (P< 0.05), and CCN2 mRNA increased (P< 0.05). After 12, 24, 36, and 48 hours, the apoptosis rate of the reaction group at different time points was higher than that of the control group (P< 0.01). When YAP-TEAD was down-regulated, the in vitro proliferation ability of BT 549-YAP cells was weakened compared with BT 549/NC and parental cells. It was concluded that the non-coding RNA LINC00857 can target the transcription factor YAP-TEAD in the Hippo signaling pathway to decrease its expression, thus inhibiting the proliferation, migration, and invasion of cancer cells, and promoting cell apoptosis.